The ethics of online research - Woodfield, Kandy (Emerald Publishing Limited, 2018)
This volume focuses on the ethics of internet and social networking research exploring the challenges faced by researchers making use of social media and big data in their research. The internet, the world wide web and social media - indeed all forms of online communications - are attractive fields of research across a range of disciplines. They offer opportunities for methodological initiatives and innovations in research and easily accessed, massive amounts of primary and secondary data sources. This collection examines the new challenges posed by data generated online, explores how researchers are addressing those ethical challenges, and provides rich case studies of ethical decision making in the digital age.
Keywords: Internet research -- Moral and ethical aspects.; Social media -- Research -- Moral and ethical aspects.; Online social networks -- Research -- Moral and ethical aspects.; Social sciences -- Research -- Moral and ethical aspects.; elektronické knihy; electronic books